Sistem Pendukung Keputusan Pemilihan Calon Desainer dengan Kombinasi Metode Rank Orde Centroid (ROC) dan Vikor - Annisa, Nur (CV. Graha Mitra Edukasi, 2023)
In companies engaged in advertising, the role of designers is very important for the sustainability of a project, designers must always be able to realize new innovations in every work carried out. The role of a reliable designer in the company is quite large, so that the acceptance of prospective new designers to accompany every job that is done in the company really requires a serious selection. This study discusses the selection of designer candidates who at least match the existing criteria, so that they cannot be accepted by the company, this research was appointed based on the difficulty of the company's personnel in selecting prospective designers manually. Data analysis was carried out so that it could determine the criteria of existing alternatives, and weighted using the ROC method and determining the ranking using the Vikor method. The results of this study are in the form of ranking at the end of the smallest order so that prospective designer candidates are obtained who do not match the criteria required by the company.